Service user perspectives on social prescribing services for mental health in the UK: a systematic review. (May 2023) - Cooper, M; Flynn, D; Avery, L; Ashley, K; Jordan, C; Errington, L; Scott, J
Aim: To thematically synthesise adult service users' perspectives on how UK-based social prescribing services support them with their mental health management. Methods: Nine databases were systematically searched up to March 2022. Eligible studies were qualitative or mixed methods studies involving participants aged ⩾ 18 years accessing social prescribing services primarily for mental health reasons. Thematic synthesis was applied to qualitative data to create descriptive and analytical themes. Results: 51, 965 articles were identified from electronic searches. Six studies were included in the review ( n = 220 participants) with good methodological quality. Five studies utilised a link worker referral model, and one study a direct referral model. Modal reasons for referral were social isolation and/or loneliness ( n = 4 studies). Two analytical themes were formulated from seven descriptive themes: (1) person-centred care was key to delivery and (2) creating an environment for personal change and development. Conclusions: This review provides a synthesis of the qualitative evidence on service users' experiences of accessing and using social prescribing services to support their mental health management. Adherence to principles of person-centred care and addressing the holistic needs of service users (including devoting attention to the quality of the therapeutic environment) are important for design and delivery of social prescribing services. This will optimise service user satisfaction and other outcomes that matter to them.